An overall thermal transfer value (OTTV) - based approach in analysing the energy efficiency of buildings : a review / Afiqah Ahmad, Wan Abdullah Wan Alwi and Azman Zainonabidin - Afiqah, Ahmad; Wan Abdullah, Wan Alwi; Azman, Zainonabidin (2015)
A building envelope thermal heat gains plays a big part in the energy consumption and the buildings energy performance. Several thermal heat gains forecasting of a building envelope has been developed such Overall Thermal Transfer Value (OTTV) to help strategize the design of a building envelope and to reduce the energy consumption of a building. An OTTV is a measuring method of the energy consumption of building envelope. This paper provides a review on the role of OTTV in its approach to analyse the energy efficiency of buildings. Previous works concerning the mathematical calculation on analysing energy consumption using OTTV is also introduced. Other related methods for measuring energy consumption performance of buildings may also be presented.